2014
DOI: 10.1111/cpsp.12060
|View full text |Cite
|
Sign up to set email alerts
|

The role of parenting in childhood anxiety: Etiological factors and treatment implications.

Abstract: Theoretical models of anxiety disorders suggest that family processes and parenting are important factors in the development, maintenance, and transmission of childhood anxiety. The direction of effects between parenting and childhood anxiety, however, remains unclear. This review article integrates theoretical, empirical, and applied knowledge regarding the association between parenting and childhood anxiety as a means to better understand the implications of involving parents in the treatment of their childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…"Tell me a time when you were nervous") and provide developmentally appropriate explanations of these emotional terms when needed. 14 16 Sometimes, there may be disagreement between parent and child reports. 17 It is therefore important for clinicians to collect collateral information from school staff and other caregivers in the form of narratives and behavior reports to supplement their findings.…”
Section: Recommendation 1: Perform a Developmentally Appropriate Multmentioning
confidence: 99%
“…"Tell me a time when you were nervous") and provide developmentally appropriate explanations of these emotional terms when needed. 14 16 Sometimes, there may be disagreement between parent and child reports. 17 It is therefore important for clinicians to collect collateral information from school staff and other caregivers in the form of narratives and behavior reports to supplement their findings.…”
Section: Recommendation 1: Perform a Developmentally Appropriate Multmentioning
confidence: 99%
“…We hypothesized that youth in all conditions would adhere to the study protocol (as indicated by successful completion of the eight training sessions and the assessment battery), and that they would show reduced negative interpretation bias, increased positive interpretation bias, and significant improvements in social anxiety symptoms. Given research suggesting that both children’s and parents’ beliefs may maintain child social anxiety (see Negreiros & Miller, 2014), addressing both sets of maladaptive beliefs may exert additive effects on reducing child anxiety symptoms. Thus, we hypothesized that participants in the Combo condition would improve the most.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of structure, particularly for youth living in high risk environments, has been associated with internalizing problems (McKee et al, 2013). Alternatively, parental overcontrol also has been associated with youth internalizing problems (Drake & Ginsburg, 2012; Neigreiros & Miller, 2014). And, of relevance, the two dimensions of overcontrol that account for the most variance in internalizing problems (i.e., anxiety symptoms) are overinvolvement and failure to grant autonomy (i.e., excessive levels of firm control; Drake & Ginsburg, 2012; McLeod, Wood & Weisz, 2007).…”
Section: Discussionmentioning
confidence: 99%